The Role of Organizational Culture in Enhancing Employee Engagement in the Era of Disruption - Musafak Khoiri; Umar Burhan; Suharto Suharto (BADAN PENERBIT STIEPARI PRESS, 2025)
In the era of disruption, employee engagement has emerged as a strategic imperative for organizational resilience and productivity. This study explores the role of organizational culture in sustaining employee engagement amid technological transformation, remote work, and economic uncertainty. Using a qualitative exploratory method, data were collected through in depth interviews with managers and employees from a private organization in Gresik, Indonesia. The findings reveal that core cultural values agility, inclusiveness, and empowerment play a crucial role in enhancing employees’ emotional commitment and motivation during times of change. These values foster psychological safety, proactive behavior, and organizational belonging. The study further demonstrates that organizational culture serves as both a mediator and moderator in the relationship between external disruptions and employee engagement. Theoretically, this research contributes to engagement literature by contextualizing it within culture driven frameworks, while practically, it offers HR professionals and leaders a roadmap for shaping adaptive cultures that preserve engagement during uncertainty. The study also discusses the limitations of its qualitative approach and recommends future research to validate the findings across various industries.